2011
DOI: 10.1128/ec.00158-10
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Hap43 Is a Repressor Induced under Low-Iron Conditions and Is Essential for Iron-Responsive Transcriptional Regulation and Virulence

Abstract: Candida albicans is an opportunistic fungal pathogen that exists as normal flora in healthy human bodies but causes life-threatening infections in immunocompromised patients. In addition to innate and adaptive immunities, hosts also resist microbial infections by developing a mechanism of "natural resistance" that maintains a low level of free iron to restrict the growth of invading pathogens. C. albicans must overcome this irondeprived environment to cause infections. There are three types of iron-responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(206 citation statements)
references
References 93 publications
14
191
0
Order By: Relevance
“…albicans Hap43p is a repressor that is induced under low-iron conditions and is essential for ironresponsive transcriptional regulation and virulence (Hsu et al, 2011). Consistent with downregulation of C. albicans iron-regulated proteins in mixed biofilms, we found that 19.71% (16) of differentially expressed proteins in mixed biofilms are Hap43p regulated (Supplementary Table S2).…”
Section: Drug-resistance Proteins and Other Outer Membrane Proteins Asupporting
confidence: 62%
“…albicans Hap43p is a repressor that is induced under low-iron conditions and is essential for ironresponsive transcriptional regulation and virulence (Hsu et al, 2011). Consistent with downregulation of C. albicans iron-regulated proteins in mixed biofilms, we found that 19.71% (16) of differentially expressed proteins in mixed biofilms are Hap43p regulated (Supplementary Table S2).…”
Section: Drug-resistance Proteins and Other Outer Membrane Proteins Asupporting
confidence: 62%
“…3C). LexA-Gcn4 and LexA constructs served as positive and negative controls, respectively (31). Compared to wild-type cells, Gat1 and Stp1 showed relatively higher transcriptional activity in cells on the rhb1-deleted background.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the DNA fragment containing the entire GAT1 gene was PCR amplified from the SC5314 genome by the use of primer pair CaGAT1-5= and CaGAT1-3=. The fragment was purified, digested with MluI and PstI, and cloned into the plasmid pCIplexA-F1 (31,64) to generate pCIpLexA-F-Gat1. The plasmid was linearized with StuI, and the lexA-GAT1 fusion fragment was introduced into the RPS1 locus in COP1 and CCR1 strains (31) to generate COP-LexAGat1 and CCR-LexAGat1.…”
Section: Methodsmentioning
confidence: 99%
“…Hap43 has been demonstrated to interact with Tup1 (30). This overlapping regulation between Rca1 and Hap43 targets further suggests that Tup1 may be involved in the mode of action of Rca1.…”
Section: Figmentioning
confidence: 95%